Enchanted Trails - Gantner, Ben (Albuquerque Journal Albuquerque, New Mexico, 1977)
Newspaper article on Raton, New Mexico in 1977 and the recreational activities, tourist attractions. Also on what Raton and the surrounding area offers.
Master list item #: 25
File location is in the Raton file Cabinet
Keywords: Brown, Wesley; La Mesa Park Horse racing track; Vermejo Park; Penzoil; Philmont Scout Ranch; Boys Scouts of America; NRA; Raton Ski Basin; City of Bethlehem; Raton Lions Club; Elks Club Lodge; Santa Fe Railroad; Local History; Life and Customs; Tourist; Railroad; Coal Mining; Cattle Ranching; Horse racing; Winter Sports; Shooting range; Skiing; Camping; Fishing; Hunting; Hiking; Golfing; Christmas display; Raton, New Mexico; Colfax County; Texas; Oklahoma; Kansas; Colorado